Pediatric trauma primary survey performance among surgical and non-surgical pediatric providers in a Brazilian trauma center - Luke Caddell; Lina Roa; David P Mooney; Fabio Botelho; Paul Truche; Kathrin Zimmerman; Nivaldo Alonso; Alexis Bowder; Domingos Drumond; Simone de Campos Vieira Abib (Trauma Surgery & Acute Care Open, 2020)
Introduction Trauma is the leading cause of death and disability among Brazilian children and adolescents. Trauma protocols such as those developed by the Advanced Trauma Life Support course are widely taught, but few studies have assessed the degree to which the use of protocolized trauma assessment improves outcomes. This study aims to quantify the adherence of trauma assessment protocols among different types of frontline trauma providers.Methods A prospective observational study of pediatric trauma care in one of the busiest Latin American trauma centers was conducted during 6 months. Trauma primary survey assessments were observed and adherence to each step of a standardized primary assessment protocol was recorded. Adherence to the assessment protocol was compared among different types of providers, the time of presentation and severity of injury. The relationship between protocol adherence and clinical outcomes including mortality, length of hospital stay, admission to pediatric intensive care unit, use of blood components, mechanical ventilation and number of imaging exams performed in the first 24 hours were also assessed.Results Emergency department evaluations of 64 patients out of 274 pediatric admissions were observed over a period of 6 months. 50% of the primary assessments were performed by general surgeons, 34.4% by residents in general surgery and 15.6% by pediatricians. There was an average adherence rate of 34.1% to the trauma protocol. Adherence among each specific step included airway: 17.2%; breathing: 59.4%; circulation: 95.3%; disability: 28.8%; exposure: 18.8%. No differences between specialties were observed. Patients with a more thorough primary assessment underwent fewer CT scans (receiver operating characteristic curve area: 0.661; p=0.027).Conclusions Our study demonstrates that trauma assessment protocol adherence among trauma providers is low. Thorough initial assessment reduced the use of CT scans suggesting that standardized pediatric trauma assessments may be a way to reduce unnecessary radiological imaging among children.Level of evidence IV.Study type Pediatric and global trauma.